Spark Venture Solutions : Glow In The Dark Gloves / Muhammad Afif Azry Muhammad Alia...[et al.] - Muhammad Alias, Muhammad Afif Azry; Daeng Johar, Tengku Daeng Iqbal Adib; Mohammad Rasid, Nazrul Syaari; Abdol Mutalib, Muhammad Helmi; Amir Hamzah, Nor Salina (2019)
The gloves industry is a wide and stable industry where the demands are increasing constantly due to the increase in population. This industry is one of the most influential industries to the income of the nation. Here in Malaysia alone, the recent population statistics have reached over 30 million capacities. With the increase in population, the demand of glove will very much likely to be increased. This type of industry demand will never be depleted as electrical glove is a must for everyone in nowadays life. The production of gloves which is made from a high-quality leather fabric will surely have a long-time shelf. This allows our company to sell the products overseas increasing the market size and sales of company.